Cambodia : Joint Bank-Fund Debt Sustainability Analysis 2018 Update - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
The Debt Sustainability Analysis (DSA) using the revised joint IMF/WB Debt Sustainability Framework for Low Income Countries (LIC-DSF) shows that Cambodia remains at low risk of external debt distress. All debt burden indicators are projected to remain under their indicative thresholds under the baseline and the shock scenarios. While the overall risk of debt distress is low, the analysis indicates that debt sustainability is vulnerable to export and growth shocks, and the materialization of contingent liabilities. Furthermore, the public and publicly guaranteed (PPG) debt-to-GDP ratio is projected to rise by more than 10 percentage points during the next decade due to projected large fiscal deficits in the medium term. These findings reinforce the importance of implementing reforms to increase the economy’s resilience to external shocks and encourage export and economic diversification. Efforts to mobilize fiscal revenue, to strengthen the Public Investment Management framework (including for PPPs) and further enhance monitoring of PPP and financial sector risks, as well as introduction of a debtbased fiscal anchor, are necessary to ensure debt sustainability in the medium term.